2015
DOI: 10.1063/1.4921792
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic condensation in spatially separated one-dimensional systems

Abstract: We show theoretically that excitons can form from spatially separated one-dimensional ground state populations of electrons and holes, and that the resulting excitons can form a quasicondensate. We describe a mean-field Bardeen-Cooper-Schrieffer theory in the low carrier density regime and then focus on the core-shell nanowire giving estimates of the size of the excitonic gap for InAs/GaSb wires and as a function of all the experimentally relevant parameters. We find that optimal conditions for pairing include… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Recently ref. 24 discussed a quasi-condensate of excitons in coupled electron-hole one-dimensional wires using the weak-coupled BCS gap equation in the low density limit with only the lowest subband contributing to the pairing, and with screening neglected. Since only one channel was considered, there are no shape resonance effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently ref. 24 discussed a quasi-condensate of excitons in coupled electron-hole one-dimensional wires using the weak-coupled BCS gap equation in the low density limit with only the lowest subband contributing to the pairing, and with screening neglected. Since only one channel was considered, there are no shape resonance effects.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, ref. 24 argues that even in the one-channel case, the finite size of the nanoribbons would allow for short range superfluid correlations. In our case the many available channels due to the multiple subbands involved in the pairing allow for a suppression of the critical fluctuations, which would favour the observation of conventional long-range superfluidity.…”
Section: Methodsmentioning
confidence: 99%
“…The results presented in this work could also be used to consider building up topologically nontrivial 1D excitonic condensates. Recent theory has shown that a core-shell nanowire with band inversion is an interesting platform for the experimental realization of excitonic condensation27.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the multi-layer samples are of higher quality than the corresponding single-layer ones, and it is therefore essential that theoretical investigation tackle those more complex, multi-flavor systems. Furthermore, the same method can be used to study lower-dimensional excitonic bound states, which have been recently proposed in two parallel nanowires [55]. This problem will be analyzed in future work.…”
Section: Discussionmentioning
confidence: 99%